Human papillomavirus vaccine effectiveness by age at first vaccination among Japanese women. Issue 4 (2nd February 2022) - Onuki, Mamiko; Yamamoto, Kasumi; Yahata, Hideaki; Kanao, Hiroyuki; Yokota, Harushige; Kato, Hisamori; Shimamoto, Kumi; Takehara, Kazuhiro; Kamiura, Shoji; Tsuda, Naotake; Takei, Yuji; Shigeta, Shogo; et al.
Abstract: In Japan, the National Immunization Program against human papillomavirus (HPV) targets girls aged 12‐16 years, and catch‐up vaccination is recommended for young women up to age 26 years. Because HPV infection rates increase soon after sexual debut, we evaluated HPV vaccine effectiveness by age at first vaccination. Along with vaccination history, HPV genotyping results from 5795 women younger than 40 years diagnosed with cervical intraepithelial neoplasia grade 2‐3 (CIN2‐3), adenocarcinoma in situ (AIS), or invasive cervical cancer were analyzed. The attribution of vaccine‐targeted types HPV16 or HPV18 to CIN2‐3/AIS was 47.0% for unvaccinated women (n = 4297), but 0.0%, 13.0%, 35.7%, and 39.6% for women vaccinated at ages 12‐15 years (n = 36), 16‐18 years (n = 23), 19–22 years (n = 14), and older than 22 years (n = 91), respectively, indicating the greater effectiveness of HPV vaccination among those initiating vaccination at age 18 years or younger ( P  < .001). This finding was supported by age at first sexual intercourse; among women with CIN2‐3/AIS, only 9.2% were sexually active by age 14 years, but the percentage quickly increased to 47.2% by age 16 and 77.1% by age 18. Additionally, the HPV16/18 prevalence in CIN2‐3/AIS was 0.0%, 12.5%, and 40.0% for women vaccinated before (n = 16), within 3 years (n = 8), and more than 3 years after (n = 15) first intercourse, respectively ( P  = .004). In conclusion, our data appear to support routine HPV vaccination for girls aged 12‐14 years and catch‐up vaccination for adolescents aged 18 years and younger in Japan. Abstract : The MINT study is the largest nationwide study monitoring human papillomavirus (HPV) vaccination impact and HPV genotype‐specific disease incidence in Japan. Our data revealed complete protection against HPV16/18‐positive cervical intraepithelial neoplasia grade 2‐3/adenocarcinoma in situ among girls vaccinated before 15 years old or sexual debut and higher HPV vaccine effectiveness among those vaccinated at 18 years old or younger.